BREAST FEEDING: RESULTS OF A RETROSPECTIVE MULTICENTER SURVEY OF A LEVEL OF FUTURE DOCTOR’S EDUCATION - Ya.Ya. Yakovlev; F.K. Manerov; V.I. Furtsev; L.F. Kaznacheeva; E.A. Surovikina; Yu.F. Lobanov; D.V. Pechkurov; N.A. Barabash; E.F. Lukushkina; A.G. Lebedev; S.N. Shishatskaya (Вопросы современной педиатрии, 2011)
Breast feeding is «the golden standard»of childern’s nutrition on their first year of life. Basic knowledge in this field is given to future medical professionals throughout their years of study in a medical school. Study objective: to assess whether knowledge and skills that future doctors possess in the field of maintaining of breast feeding is adequate to modern requirements. Methods: as a part of retrospective cross-section study a questionnaire was given to medical students of two final years as well as to interns and residents.  Results: in 2010–2011 the total of 1088 medical students from 8 medical schools and Novokuznetsk Institute of Advanced Medical Studies was questioned. 64.9% from the total were from pediatric faculty and 35.1% on a general medical faculty. The proportion of correct answers to theoretic questions was more than 85%. However the majority of students experience difficulties with implying this knowledge to solve practical cases. No major differences in replies given by pediatric and medical students were found. Conclusion:  The «alienation» of theoretic knowledge that students possess from its practical implication doesn’t help to solve problems with maternal lactation. Therefore it’s necessary to pay more attention to practical implication of theoretical knowledge given to medical students, especially upon infantile nutrition. Key words: breast feeding, student education. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 10–16.)